2004
DOI: 10.4314/eamj.v81i5.9169
|View full text |Cite
|
Sign up to set email alerts
|

Retinitis pigmentosa in Benin, Nigeria

Abstract: Objectives: To determine the mode of presentation and degree of visual impairment of retinitis pigmentosa in Nigerians. Design: A prospective, non-comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 13 publications
8
17
9
Order By: Relevance
“…The mean age of 39 years in this study is similar to the 36.7 years reported in a single center study from southern Nigeria8 and the 35.1 years in Japan 15. Eballe et al,10 however, reported a higher mean age of 43.3 years in a Cameroonian hospital; late presentation for eye care was the reason reported for the high mean age in that study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The mean age of 39 years in this study is similar to the 36.7 years reported in a single center study from southern Nigeria8 and the 35.1 years in Japan 15. Eballe et al,10 however, reported a higher mean age of 43.3 years in a Cameroonian hospital; late presentation for eye care was the reason reported for the high mean age in that study.…”
Section: Discussionsupporting
confidence: 85%
“…RP presents clinically with varied ocular symptoms; night blindness is usually the initial symptom followed by loss of visual field and visual acuity as the disease progresses 1,3,8. It evolves over several decades and final loss of central vision may not occur until the age of 60 years 1,9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male preponderance was present in the studies reported from Beijing, Denmark and Nigeria. 8,13,17 No statistically significant regional preponderance (rural vs. urban) was noted in the subjects with RP in our study. Notably 2 (15.38%) subjects were relatively asymptomatic whereas others complained of decrease of vision.…”
Section: Discussioncontrasting
confidence: 60%
“…19 Poor vision is the commonest mode of presentation in Nigeria with over 50% presenting blind. 20 Low visual aids and Braille education remain important sources of visual rehabilitation depending on the level of visual loss.…”
Section: Discussionmentioning
confidence: 99%